Food Nitrogen Footprint of the Indian Subcontinent Toward 2050 - Dhar, Aurup Ratan; Oita, Azusa; Matsubae, Kazuyo (Frontiers in Nutrition, 2022)
Substantial loss of nitrogen (N) in reactive forms (nitrogen species except for N2) induced by agro-food system is a cause of environmental degradation and harms human health. The main factors influencing the food N footprint of the Indian subcontinent (ISC) are the nitrogen use efficiency (NUE) of crop cultivation and religious dietary cultures. In this study, we assess the food N footprint of the ISC and establish reduction scenarios towards 2050. We used a religion-sensitive N-Calculator method and food consumption data from the Food and Agriculture Organization of the United Nations to estimate the food N footprint of the ISC of different religious communities. We developed four reduction scenarios: the business-as-usual scenario; a 30% increase in the crop cultivation NUE; altered protein supplies to the healthy EAT-Lancet reference diet considering religious food taboos; and an integrated approach with a 30% increase in the NUE increase and the altered diet. We used the long short-term memory recurrent neural network approach to predict the future. The study revealed that the average food N footprint per-capita per-year increased from 7.94 kg-N in the 1960s to 8.43 kg-N in the early 2010s, and the crop cultivation NUE was reduced to less than 40%. Buddhists had the lowest footprint over the period. An increase in the NUE of the crop cultivation and an altered diet results in a 13% reduction in the N footprint compared to the business-as-usual scenario. We conclude that improved crop cultivation NUEs and an altered religion-specific healthy diet would reduce the N footprint.